2014
DOI: 10.15748/jasse.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Biomolecular Chemical Computations toward the Prediction of <i>Burkholderia cepacia</i> Lipase Enantioselectivity

Abstract: We have performed the molecular dynamics (MD) and the fragment molecular orbital (FMO) calculations on the complexes of Burkholderia cepacia lipase (BCL) with alcohol esters toward the prediction of lipase enantioselectivity. The MD computations show that for esters of high enantioselectivity, the difference in the CO interatomic distance between (R)-and (S)-enantiomer complexes is more than 9.0Å, while for esters of low enantioselectivity, the difference is less than 3.0Å. In addition, the FMO computations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…As an alternative to manual preprocessing, an automated preprocessing approach was also initiated by the development working group of the FMODD reported as Auto-FMO protocol (Figure ). As reported from many previous studies, ,,,, ,, if only a small number of biopolymers are to be subjected to FMO calculation, manual processing using visual inspection and trial and error can be conducted. However, the manual approach is not practical for anything more than a few hundred complexes of drug target proteins and certainly not for the more than 160 000 experimental structures registered in the PDB, so an automatic pretreatment protocol, which was named as Auto-FMO protocol (Figure ), was developed with pipeline pilot .…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to manual preprocessing, an automated preprocessing approach was also initiated by the development working group of the FMODD reported as Auto-FMO protocol (Figure ). As reported from many previous studies, ,,,, ,, if only a small number of biopolymers are to be subjected to FMO calculation, manual processing using visual inspection and trial and error can be conducted. However, the manual approach is not practical for anything more than a few hundred complexes of drug target proteins and certainly not for the more than 160 000 experimental structures registered in the PDB, so an automatic pretreatment protocol, which was named as Auto-FMO protocol (Figure ), was developed with pipeline pilot .…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, we have performed biomolecular chemical simulations, including MD calculation and FMO calculation, on the complexes of BCL and CALB with various primary and secondary alcohol esters. 5,6 We have shown that our simulation is a useful tool for predicting the enantioselectivity of BCL and CALB for various alcohol esters. 5,6…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, we are focusing on biomolecular chemical simulations on the complexes of lipases and organic compounds to predict the enantioselectivity and reactivity of lipase in organic synthesis, and have selected lipases such as Burkholderia cepacia lipase (BCL) and Candida antarctica lipase typeB (CALB) as target proteins. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…As shown in our previous works [7,19], the IFIE analysis is a useful method for gaining detailed information on protein-ligand binding. For the esters with high enantioselectivity, each fast reacting enantiomer showed a strong interaction with Thr40 in CALB.…”
Section: Fragment Molecular Orbital Calculationsmentioning
confidence: 99%
“…Over the last several years, we have been focusing our attention on biomolecular chemical simulations of the complexes of lipases with organic compounds to elucidate the enantioselectivity and reactivity of these enzymes in organic synthesis. We have recently shown that both molecular dynamics (MD) and fragment molecular orbital (FMO) calculations are useful means for the prediction of the enantioselectivity of BCL toward a variety of primary and secondary alcohol esters [7]. In this paper, we performed MD and FMO calculations toward CALB complexes with eight different primary alcohol esters ( Figure 1) and thirteen different secondary alcohol esters ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%